Beyond density: Mesostructural features of impact resistant wood. (March 2020) - Matsushita, A.K.; Gonzalez, D.; Wang, M.; Doan, J.; Qiao, Y.; McKittrick, J.
Abstract: Wood is a neglected impact-resistant biological material: despite its use in tools and weapons for millennia the dynamic properties and common features between species such as maple, live oak, and others are poorly understood. In this study, the impact resistance in the radial loading direction of nine tree species was studied using drop-tower testing, micro-computed tomography, and scanning electron microscopy. It was found that unlike in quasi-static conditions, density alone is a poor predictor of mechanical behavior in wood and that specific mesostructural features (interlocking grain, diffuse porous vessel distribution and intermittent rays) improved impact strength. A new, hierarchical failure of individual tracheids and the bulk fibers resembling progressive delamination of fiber-composites was observed in African mahogany, the most impact resistant tree species tested.